Pemberdayaan Masyarakat Melalui Gotong Royong dalam Perbaikan Saluran Air untuk Mencegah Banjir Lingkungan di RT 003 RW 005 Kelurahan Sidomulyo Timur, Kecamatan Marpoyan Damai, Kota Pekanbaru - Wicaksono, Agung; Wardana, Data; Andry, Hendry (Jurnal Pengabdian Kepada Masyarakat Patikala, 2026)
Environmental flooding frequently occurs in RT 003 RW 005, Sidomulyo Timur Village, Pekanbaru, posing a significant problem that disrupts daily activities and threatens residents’ health. One of the main causes is clogged drainage channels due to waste accumulation and sediment buildup. This community service program aims to empower residents through collective action (gotong royong) to repair and clean the drainage system. The program was implemented with funding support from the Research and Community Service Institute (DPPM) of Universitas Islam Riau. The methods used include community outreach, technical training, joint clean-up activities, and continuous assistance. The results show substantial improvements in the drainage channels, reduced flood risk, increased environmental awareness, and the formation of an active and sustainable environmental care community. This empowerment model has generated positive and lasting social and environmental impacts.